2013
DOI: 10.1589/jpts.25.509
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Affecting Subjective Symptoms of Fatigue Due to the Environment of High School Students’ Computer Workstation in the Republic of Korea

Abstract: Abstract. [Purpose] This study aimed to determine the risk factors influencing subjective symptoms of fatigue through computer workstation monitoring of Korean high school students.[Methods] Six-hundred and eighty-five high school students were surveyed, and the independent t-test and one-way ANOVA were conducted to determine subjective symptoms of fatigue according to gender and hours of computer use, respectively. Pearson correlation coefficients were calculated to examine the correlations between subjectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Prevention and management require investigation both of the incidence of MSD by job category, as well as of the basic causes 3 ) . Work-related MSDs are caused by various and complex factors 4 ) , which must be considered in order to identify the major causes, and to examine the associations among the factors causing the MSDs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevention and management require investigation both of the incidence of MSD by job category, as well as of the basic causes 3 ) . Work-related MSDs are caused by various and complex factors 4 ) , which must be considered in order to identify the major causes, and to examine the associations among the factors causing the MSDs.…”
Section: Introductionmentioning
confidence: 99%
“…Dental practitioners reportedly have a higher likelihood of MSDs, because they work in a static posture using their hands and wrists, while their backs, shoulders, and legs are bent. In fact, 64–96% of dental practitioners reportedly experience MSD pain 3 , 4 , 10 ) . In dental hygienists, 60–69.5% reported that MSD pain occurred primarily in the hand and wrist regions, whereas in dentists, 36.3–60.1% and 19.8–85% reported that MSD pain occurred in the back and neck regions, respectively 4 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Yoo et al 9 ) suggested that improved computer workstations could prevent musculoskeletal disorders. A previous study also found that differences in computer workstations were associated with differences in fatigue 10 ) . The present study found that the use of dual monitors increased orbicularis oculi activity; therefore, to decrease eye fatigue in computer users, computer workstations that use either a single monitor or identical monitors from the same manufacturer in a dual setup, are recommended.…”
Section: Discussionmentioning
confidence: 84%